The best Easter prize - Evans, Kristina; Wallace, John (New York : Cartwheel Books, 2010)
Monica and her friends are busy gathering eggs on the annual Easter Egg hunt when she notices a little girl sitting on a rock who has no eggs, so Monica decides to share hers.
Keywords: Children's stories